Digital transformation in accounting: Emerging technologies, ethics, and regulation - Sudirman, Amalia (Jurnal Akuntansi dan Auditing Indonesia, 2026)
Over the past two decades, numerous studies have explored the intersection of technology and accounting. However, research that specifically examines digital transformation in accounting particularly concerning emerging technologies, ethical risks, and regulatory challenges remains fragmented. Therefore, the purpose of this study is to conduct a bibliometric analysis of scholarly works addressing digital transformation in accounting. This study adopts a systematic literature review approach, analyzing articles containing the terms “digital transformation,” “accounting,” and related keywords in the “Article Title, Abstract, and Keywords” fields of the Scopus database from 2006 to 2025. The final dataset was compiled and analyzed using VOSviewer software to identify key research trends, co-authorship networks, and thematic clusters. The findings show that research on digital transformation in accounting has grown significantly since 2020, with increased attention to technologies such as artificial intelligence (AI), blockchain, and cloud computing. However, ethical and regulatory dimensions remain underexplored, indicating a research gap. In addition, contributions are concentrated in developed countries, with limited studies from emerging economies, suggesting a need for more globally inclusive research. The study offers insights for practitioners, regulators, and educators to better align digital adoption with ethical principles and regulatory frameworks in accounting. The findings contribute to fostering trust, transparency, and accountability in the digital transformation of accounting, which is essential for both professional integrity and public confidence.